Depression, Anxiety and Quality of Life in Greek Hospital Staff: A Study in the Aftermath of the Debt Crisis Era - Melemeni, Despoina; Mantzouranis, Konstantinos; Georgakopoulou, Vasiliki Epameinondas; Tarantinos, Kyriakos; Garmpis, Nikolaos; Damaskos, Christos; Sklapani, Pagona; Chlapoutakis, Serafeim; Trakas, Nikolaos; Tsiafaki, Xanthi; Papathanasiou, Ioanna V. (Acta medica Lituanica, 2021)
Background: Several studies investigated the mental health needs of hospital staff in Greece during the debt crisis era. Yet, no relevant data are available regarding the mental health of hospital staff after this period. The aims of this study are: 1) To investigate the prevalence of clinically significant depression and anxiety in healthcare workers in a general hospital in Athens, Greece; 2) to search for the association of quality of life with anxiety and depression in those workers; 3) to investigate the association of sociodemographic characteristics with those parameters. Methods: The Zung Depression Rating Scale, the Zung Anxiety Rating Scale, the Short-Form Survey-12, assessing quality of life, and sociodemographic assessments were administrated in 110 workers of a public hospital in Athens, Greece. The assessments were completed during January, 2020. Results: Of the study participants, 38.2% had clinically significant anxiety and 6.4% had clinically significant depression. Males had lower scores of depression compared to females (p=0.003). As for the effects of educational level, differences were noted in psychological quality of life between secondary education participants when compared to tertiary education (Mean Difference -3.527, p=0.021), post-graduate (Mean Difference -3.937, p=0.012) and PhD participants (Mean Difference -5.100, p=0.007). Quality of life and its psychological and physical health subscales had strong inverse associations with depression and anxiety (p=0.000). Conclusions: Relevant interventions are necessary to decrease anxiety in hospital staff, which is elevated in the aftermath of the debt crisis period. In addition, health policy makers have to reduce the gender gap in mental health between male and female workers, since the latter had higher levels of depression.